Carboidrases associadas às altas doses de fitase em dietas para frangos de corte - Sangalli, Gabriela Glaeser (2019)
The aim of this study was to evaluate phytase overdoses associated with carbohydrates in diets with nutritional reduction on performance, carcass and cut yields, relative weight of organs of the gastrointestinal tract, intestinal morphometry, digestion viscosity, pH of intestinal and cecal contents, quality of bedding, bone and blood parameters of broilers. For this purpose, 1,540 male day-old broiler chicks were used, distributed in a completely randomized design with five treatments, 14 repetitions with 22 birds per experimental unit. The treatments consisted of: positive control (CP): ration based on corn and soybean meal with the inclusion of meat meal and offal meal without enzymes; negative control (CN): CP diet with a reduction of 100 kcal, 0.15% P, 0.12% Ca, 4% AA and 5% Na; CN feed + carbohydrase + phytase (1000, 1500 and 2000 FTU kg-1). The data obtained were subjected to analysis of variance and the means compared by the Tukey test (P <0.05). The birds that received dietary inclusion of enzymes showed weight gain (GP) and feed conversion (CA) similar to the CP group in the initial period (1 to 7 days). From 1 to 21 days, the birds that received enzymes showed higher GP and better CA when compared to the CN group. For the total period (1 to 42 days) the birds that received feed with the different levels of enzyme showed similar CA to the birds of CP and CN. At 21 days, the birds in the CN treatment showed a higher relative weight of the pancreas in relation to the other treatments and a higher relative weight of the small intestine in relation to the birds that received enzymatic supplementation. For the cecal pH, at 21 days, the birds of the CN showed lower value when compared to the birds of the treatments with 1500 and 2000 FTU. At 42 days, the birds of the CP have lower pH cecal in relation to the birds of the treatments with 1000 and 1500 FTU. Birds that received CN had lower ammonia content in bed at 42 days compared to other treatments. The inclusion of carbohydrase associated with different levels of phytase did not change the other parameters evaluated. For bone parameters at 21 and 42 days, there was no difference (P> 0.05) between treatments regarding rupture resistance, seeder index, density and growth plate. For mineral matter and calcium and phosphorus contents of the tibial bones at 21 and 42 days of age, there was no difference (P> 0.05) between treatments. Regarding blood parameters at 21 days, the concentrations of Ca and P in the blood were higher in birds that received 1000 FTU kg-1. For triglycerides, birds of the CN diet and 1000 FTU kg-1 showed higher concentrations. For alkaline phosphatase birds that received a diet with 1500 FTU kg-1 showed lower concentration when compared to CP. Glucose and total protein showed no difference (P> 0.05). At 42 days, the concentration of Ca, P and PT was higher in birds that received the CP diet. For glucose, the highest concentration was in birds that received 2000 FTU kg-1 compared to those that received 1000 FTU kg-1. For triglycerides the concentration was lower in birds that received 1000 and 1500 FTU kg-1. There was no difference for alkaline phosphatase (P> 0.05). The use of phytase associated with carbohydrases in diets with nutritional reduction maintained the birds' performance in the pre- initial phase. In the growth phase, the performance of these birds was superior to the CN treatment, not equaling the CP. The addition of carbohydrases associated with 1000 FTU kg-1 phytase provided an increase in serum calcium, phosphorus and total protein of the birds at 21 days. At 42 days, birds on the CP diet showed higher levels of calcium and phosphorus and the inclusion of enzymes reduced these levels, however, the bone parameters were not changed.